Correction: Zeng et al. Hedgehog Signaling: Linking Embryonic Lung Development and Asthmatic Airway Remodeling. Cells 2022, 11, 1774 - Ling-Hui Zeng; Muhammad Qasim Barkat; Shahzada Khurram Syed; Shahid Shah; Ghulam Abbas; Chengyun Xu; Amina Mahdy; Nadia Hussain; Liaqat Hussain; Abdul Majeed; Kashif-ur-Rehman Khan; Ximei Wu; et al. (Cells, 2025)
In the original publication [...]